ARTISTIC PSYCHOLOGISM IN THE WORKS OF EDGAR ALLAN POE AND ABDURAUF FITRAT (SCIENCE TIME JOURNAL, 2026)
This study explores artistic psychologism—the depiction of intricate psychological states through literary techniques—in the works of Edgar Allan Poe and Abdurauf Fitrat. Poe's gothic tales, such as "The Tell-Tale Heart" and "The Fall of the House of Usher," masterfully employ unreliable narration, sensory imagery, and stream-of-consciousness to delve into guilt, madness, and the subconscious. In parallel, Fitrat's modernist prose, including The Rose's Rebellion and Layli and Majnun, integrates Jadid reformist themes with psychological depth, portraying inner turmoil, identity crises, and spiritual awakening amid colonial pressures. By comparing their approaches, the paper reveals cross-cultural convergences in psychologism: both authors use symbolism and fragmented narratives to externalize the psyche, influencing global literary modernism. Ultimately, it argues that psychologism serves as a bridge between Romantic individualism and 20th-century existential inquiry.